2022
DOI: 10.1186/s12882-022-02906-4
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of immune cell infiltration in the glomerulus of diabetic nephropathy: evidence based on bioinformatics

Abstract: Background Increasing evidence suggests that immune cell infiltration contributes to the pathogenesis and progression of diabetic nephropathy (DN). We aim to unveil the immune infiltration pattern in the glomerulus of DN and provide potential targets for immunotherapy. Methods Infiltrating percentage of 22 types of immune cell in the glomerulus tissues were estimated by the CIBERSORT algorithm based on three transcriptome datasets mined from the GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…Similarly, by comparing host and SARS‐CoV‐2 RNA sequencing data, researchers highlighted that SERPINA3 was specifically altered in SARS‐CoV‐2‐infected respiratory cells, showing its potential as a therapeutic target to reduce the severity of COVID‐19 46 . Various studies also indicated that SERPINA3 participated in the progression of diabetes and different complications 47,48 . CLDN11 is a junctional protein associated with epithelial‐mesenchymal transition and cell–cell adhesion 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, by comparing host and SARS‐CoV‐2 RNA sequencing data, researchers highlighted that SERPINA3 was specifically altered in SARS‐CoV‐2‐infected respiratory cells, showing its potential as a therapeutic target to reduce the severity of COVID‐19 46 . Various studies also indicated that SERPINA3 participated in the progression of diabetes and different complications 47,48 . CLDN11 is a junctional protein associated with epithelial‐mesenchymal transition and cell–cell adhesion 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the presence of inflammatory infiltrates of activated immune cells is well documented in the glomeruli affected by DN, 33,34 we hypothesised that IL-8 produced by podocytes may induce the recruitment of immune cells from the circulation and the stimulation of the resident immune cells.…”
Section: Cd3+ T Lymphocytes Increase During the Progression Of Dnmentioning
confidence: 99%
“…In patients with type 2 diabetes, kidney biopsy studies indicated that the number of macrophages in the glomeruli transiently increases in the stage of moderate glomerulosclerosis, but remains low at mild and advanced stages ( 13 ). The ratio of M1/M2 macrophages is dynamically changing during the progression of DN at different stages ( 14 , 15 ). These macrophages traditionally classified into inflammatory M1 macrophages (CD68+/iNOS+) and M2 macrophages (CD68+/Arg-1+) ( 12 , 14 , 15 ).…”
Section: Dynamic Changes Of Macrophages In Dnmentioning
confidence: 99%
“…The ratio of M1/M2 macrophages is dynamically changing during the progression of DN at different stages ( 14 , 15 ). These macrophages traditionally classified into inflammatory M1 macrophages (CD68+/iNOS+) and M2 macrophages (CD68+/Arg-1+) ( 12 , 14 , 15 ). Findings from kidney biopsies showed that M1 macrophages are recruited to the kidney during the early stages of DN (Stages I and IIa).…”
Section: Dynamic Changes Of Macrophages In Dnmentioning
confidence: 99%